Patient perceptions of joint medical-surgical assessment in a tertiary referral clinic for inflammatory bowel disease. Issue 5 (2nd May 2021) - Iqbal, Nusrat; Sackitey, Charlene; Reza, Lillian; Warusavitarne, Janindra; Tozer, Phil; Hart, Ailsa
Abstract : Background: Joint medical-surgical inflammatory bowel disease clinics allow simultaneous patient assessment by both a gastroenterologist and surgeon. However, patient perceptions of dual clinician presence have not been adequately assessed. Therefore, this study aimed to evaluate the patient's view of receiving multidisciplinary care in this clinic. Methods: Patients attending the medical-surgical inflammatory bowel disease clinic completed questionnaires assessing their attitudes towards the clinic, their overall satisfaction and desired frequency of appointments. Results: Responses were received from 44 patients, the majority of whom indicated that attendance at the joint medical-surgical clinical made them feel less anxious about their disease, provided consistent messages regarding their care and minimised the number of trips made to hospital. High levels of satisfaction were reported, with 43% stating they preferred joint clinic attendance for every appointment. Conclusions: Effective inflammatory bowel disease management requires coordinated care across specialties. Simultaneous medical-surgical assessment has practical and emotional benefits, without making patients feel overburdened by the presence of more than one clinician. This supports the streamlining of care for patients with inflammatory bowel disease in specific clinical scenarios.